Does this virtual food make me hungry? effects of visual quality and food type in virtual reality - Ramousse, Florian; Raimbaud, Pierre; Baert, Patrick; Helfenstein-Didier, Clémentine; Gay, Aurélia; Massoubre, Catherine; Galusca, Bogdan; Lavoué, Guillaume (Frontiers in Virtual Reality, 2023)
Studies into food-related behaviors and emotions are increasingly being explored with Virtual Reality (VR). Applications of VR technologies for food science include eating disorder therapies, eating behavior studies and sensory analyzes. These applications involve 3D food stimuli intended to elicit cravings, stress, and/or emotions. However, the visual quality (i.e., the realism) of used food stimuli is heterogeneous, and this factor's influence on the results has never been isolated and evaluated. In this context, this work aims to study how the visual quality of food stimuli, exposed in a virtual reality environment, influences the resulting desire to eat. 28 subjects without eating disorders were included in this protocol, who evaluated the desire to eat induced by 10 3D food stimuli, each duplicated in 7 quality levels (for a total of 70 stimuli). Results show that visual quality influences the desire to eat, and this effect depends on the type of food and users' eating habits. We found two significant thresholds for visual quality: the first provides the minimal quality necessary to elicit a significant desire to eat, while the second provides the ceiling value above which increasing the quality does not improve further the desire to eat. These results allow us to provide useful recommendations for the design of experiments involving food stimuli.